Plants as biosensors: Tomato plants' reaction to human voices - Fuchs, Patrick; von der Grün, Rebecca; Maslatón, Camila Ines; Gloor, Peter A. (Handbook of Social Computing, 2024)
Plants can react to a wide range of external stimuli such as light, oxygen, parasites, touch, and sound. They perceive changes in the environment and adapt their physiology accordingly. Some plants react fast and notoriously by moving or closing their leaflets, but most do it imperceptible, like tomato plants, which are the focus of this chapter. By interpreting the bioelectrochemical signals generated by the plant, valuable insights about the environment and the people in it can be gained. The human voice has different pitches depending on sex, social context, and environment conditions. This chapter aims to find out how tomato plants react to human voices of different frequencies by conducting experiments where the plant is exposed to recordings of people singing, talking, and reading, and by analyzing its reaction.<br
CRIS-Team Scopus Importer:2025-02-04